The ballot and the bullet - Catt, Carrie Chapman, 1859-1947.; Livermore, D. P. (Daniel Parker), 1818-1899.; Chapman, Charles H.; Blackwell, Alice Stone, 1857-1950.; Davis, John, 1826-1901.; National American Woman Suffrage Association; Catt, Carrie Chapman, 1859-1947; National American Woman Suffrage Association Collection (Library of Congress) (Philadelphia, Pub. for the National American woman suffrage association ... Press of A.J. Ferris, 1897)
This is a collection of essays written to refute the argument that women should not be enfranchised because they are incapable of defending their right to vote by military service.
Female warriors, by D.P. Livermore. -- The right of woman to the ballot, by C.H. Chapman. -- The military argument, by Alice S. Blackwell. -- Address before the United States Senate committee, by J. Davis.
On cover: Political science study series, vol. III, no. 3.
Also available in digital form on the Library of Congress Web site.
Keywords: Women -- Suffrage